The decade of China’s football reform: Evolutionary characteristics, performance evaluation, and reflections and insights - Zheng Li; Peng Du; Wanjin Deng; Dawei He; Xinyi Dong; Qifei Xia (PLoS ONE, 2025)
The year 2025 marks the tenth anniversary of the issuance of the General Plan of Chinese Football Reform and Development , and the deepening development of China’s football reform necessitates a robust policy framework for support. Quantitative research on policy texts enables an objective evaluation of the policy efficacy in China’s football reform. This study constructs a quantitative assessment and empirical analysis framework encompassing nine primary variables and 40 secondary variables by employing methods such as textual analysis, the Delphi method, content analysis, and the PMC index model. Combining the PMC index model with surface plots, it conducts a quantitative evaluation of ten representative national-level policy texts introduced by China. The results indicate that, the overall assessment of these ten policies is “good.” Among them, two policies (P1 and P3) are classified as exemplary policies, four (P4, P6, P7, and P8) are rated as good policies, and the remaining four are categorized as moderate policies. This suggests that while the policy design is generally scientifically sound and effective, there remains room for improvement in increasing the number of exemplary policies. The research conclusions suggest that exemplary policies exhibit characteristics of both localized top-level design and a leading-by-example effect; good policies encounter practical issues of coordinated policy design with localized deficiencies; and moderate policies still display governance phenomena of specialized institutional outputs coupled with mutual constraints. Therefore, the national strategy for China’s future football reform is characterized by longevity and gradualism, and there remains a lag in the implementation and actualization of policies. It is imperative to adopt a process-oriented mindset to achieve a substantive transformation from the advantages of policy texts to governance efficacy.